Inhibition of Acyl-CoA Synthetase Long-Chain Family Member 4 Facilitates Neurological Recovery After Stroke by Regulation Ferroptosis - Chen, Junmin; Yang, Lan; Geng, Lianxia; He, Junna; Chen, Lei; Sun, Qian; Zhao, Jing; Wang, Xiaopeng (Frontiers in Cellular Neuroscience, 2021)
Background: Ischaemic stroke is the main cause of disability worldwide, leading to a serious socioeconomic burden. Ferroptosis is a non-apoptotic form of programmed cell death and is related to various diseases. Acyl-CoA synthetase long-chain family member 4 (ACSL4) is considered a target of ferroptosis, but its specific role in ischaemic stroke remains unclear. In this study, we investigate whether the inhibition of ACSL4 promotes the recovery of neurological function in a way that prevents ferroptosis. Methods: A transient cerebral ischaemia model was established for mice by middle cerebral artery occlusion (MCAO); glutathione peroxidase 4 (GPx4), ACSL4 and cyclooxygenase 2 (COX2) were detected by Western blot, and changes to mitochondria were observed by a transmission electron microscope. A kit was used to determine iron levels and lipid peroxide indicators, such as glutathione peroxidase (GPx), reduced glutathione (GSH), total glutathione/oxidised glutathione (GSH/GSSH), lipid peroxidation, reactive oxygen species, superoxide and malonaldehyde. Following MCAO, a ferroptosis inhibitor, liproxstatin-1, was administered intranasally immediately at a concentration of 10 mg/kg. Rosiglitazone was used to inhibit ACSL4 and was administered intravenously 1 h before MCAO at a concentration of 0.4 mg/kg. Brain injury was determined by neurological deficit scores, neuroscore (28-point), corner test and gait analyses, at 24 and 72 h after MCAO. Results: After MCAO, GPx4 protein expression decreased, ACSL4 and COX2 protein expression increased, GPx activity decreased and iron accumulation. Transmission electron microscopy confirmed that the outer mitochondrial membrane of neurons had ruptured and mitochondrial cristae had decreased or disappeared. Liproxstatin-1 could significantly attenuate the decrease of GPx4 and the increase of COX2 after MCAO, dramatically reducing iron accumulation and decreasing GPx activity, accompanied by a marked reduction in changes in lipid peroxidation indicators. The use of rosiglitazone to inhibit ACSL4 could significantly improve neurological function after MCAO. Importantly, inhibiting ACSL4 could significantly attenuate the decline of GPx4 after MCAO and markedly attenuate iron accumulation and a decrease in GPx activity. Additionally, changes in lipid peroxidation indicators were also significantly inhibited. Conclusion: This study indicates that inhibiting ACSL4 can promote the recovery of neurological function after stroke by suppression of ferroptosis.